The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/echo.14098
|View full text |Cite
|
Sign up to set email alerts
|

A clinical application of preload stress echocardiography for predicting future hemodynamic worsening in patients with early‐stage heart failure

Abstract: Evaluation of a response in TMF during the LPP might provide an incremental diagnostic value to detect future overt heart failure in patients with early-stage heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Several investigators showed that the responses of mitral inflow to nitroprusside or leg lifting identified subgroups of patients who have markedly different prognoses despite similar baseline mitral inflow patterns 6,7 . In our previous papers, we used leg‐positive pressure (LPP) as an alternative technique for non‐invasive preload augmentation, and we estimated the LV diastolic reserve by the change in mitral inflow pattern 8–11 . Impaired responses to an increment during preload stress provided additional prognostic information to conventional echocardiographic parameters in HF 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators showed that the responses of mitral inflow to nitroprusside or leg lifting identified subgroups of patients who have markedly different prognoses despite similar baseline mitral inflow patterns 6,7 . In our previous papers, we used leg‐positive pressure (LPP) as an alternative technique for non‐invasive preload augmentation, and we estimated the LV diastolic reserve by the change in mitral inflow pattern 8–11 . Impaired responses to an increment during preload stress provided additional prognostic information to conventional echocardiographic parameters in HF 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In our previous papers, we used leg-positive pressure (LPP) as an alternative technique for non-invasive preload augmentation, and we estimated the LV diastolic reserve by the change in mitral inflow pattern. [8][9][10][11] Impaired responses to an increment during preload stress provided additional prognostic information to conventional echocardiographic parameters in HF. 12,13 Thus, abnormal LV diastolic response to preload stress can be an occult sign of HF.…”
Section: Introductionmentioning
confidence: 99%